Investment decisions and firm value: The moderating role of tax avoidance - Chandra, Santoso; Firmansyah, Amrie; Trisnawati, Estralita (WIM Solusi Prima, 2025)
This study aims to examine the effect of investment decisions on firm value, as well as to analyze the role of tax avoidance as a moderating variable in manufacturing companies in the consumer goods sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. This study uses secondary data obtained from the company's annual financial statements. The sample consisted of 15 companies selected using purposive sampling technique, thus obtaining 45 observations. The firm value variable is measured by the Tobin's Q ratio, investment decisions are proxied by total asset growth, while tax avoidance is proxied by the Tax Avoidance (TAXAVOID) ratio. Data analysis was carried out using panel data regression with the selected model, namely the Fixed Effect Model. The results showed that investment decisions have no effect on firm value. This finding indicates that the investment made by manufacturing companies during the study period has not been able to improve market perception directly. In addition, tax avoidance is also not proven to strengthen the relationship between investment decisions and firm value, and even tends to weaken the relationship. This study contributes to enriching the literature on the determinants of firm value in emerging markets, especially in the Indonesian manufacturing sector. In terms of policy, the results of this study suggest that regulators such as the Financial Services Authority strengthen supervision of tax avoidance practices carried out by public companies. In addition, companies are advised to improve transparency and effectiveness of investment management in order to increase investor confidence and create sustainable firm value.